Research Progress and Prospect of Green Infrastructure with Public Health Promotion Function - Tongyu LI; Junyi LIXU; Binxia XUE; Yan (USA) SONG (Fengjing Yuanlin)
ObjectiveThis research aims to explore and elucidate pathways through which green infrastructure (GI) promotes public health by constructing an integrative framework that integrates various GI types with their roles in enhancing physiological, psychological, and social well-being. Recognizing the importance of GI in urban planning to integrate natural and built environments for improving citizens’ daily life, this research addresses challenges such as fragmented classification systems, limited analysis of action pathways, and ambiguity in scale adaptation. The main objectives are to systematically classify GI types, track the development of related research, and describe the positive and negative mechanisms by which GI affects public health.MethodsA systematic review approach modelled on the PRISMA guidelines is used to collect and analyze literature from multiple disciplines including medicine, environmental sciences, and architecture. Comprehensive search is conducted in databases such as Web of Science, PubMed, Scopus, and EBSCOhost using a broad range of search terms related to GI and public health without time restrictions. After rigorous screening based on predefined inclusion and exclusion criteria, 77 relevant research articles are selected for detailed analysis. Data extraction focused on various dimensions, including specific GI types, action pathways, health outcomes, public health dimensions (physiological, psychological and social dimensions), spatial scales, and research subjects. To manage the multidimensionality of GI research, cluster analysis is performed using a Word2Vec model combined with a K-means algorithm to integrate different GI forms into a coherent classification system.ResultsThe results show that GI can be clearly divided into different categories, such as urban green spaces and parks, high-interaction spaces, trees in built-up areas, water management and biofiltration systems, community and residential greening, green roofs and facades, linear green networks, and broader macro-GI strategies. The historical development of GI research can be divided into four stages: Initial stage (2002 – 2011), during which the research focus was on thermal comfort and air quality improvement; exploration stage (2012 – 2017), during which the research scope was expanded to include disease prevention and social cohesion; prosperity stage (2018 – 2021), during which multidimensional health outcomes were integrated; and transformation stage (2022 – 2024), during which advanced technologies such as GIS, remote sensing, and machine learning were utilized. In addition, the research identifies positive pathways for GI to promote physical activity, regulate microclimate, enhance aesthetic and biodiversity benefits, and improve water quality. However, it also acknowledges potential negative effects, such as serving as habitats for disease vectors and releasing allergens that may exacerbate respiratory diseases.ConclusionThis research systematically outlines the multifaceted role of GI in public health, highlighting the need for a standardized GI health service framework that integrates various GI types with specific health outcomes and spatial scales. Such a framework could significantly enhance urban planning and policy-making by optimizing GI interventions to provide the most significant public health benefits. The findings advocate further interdisciplinary collaboration and integration of advanced data analytics to deepen our understanding of GI health pathways. Future research should focus on quantifying these benefits and developing practical evaluations to provide targeted interventions, ultimately leading to more effective public health strategies in urban settings.